2018
DOI: 10.1016/j.cell.2018.03.050
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Network Analysis Reveals Shieldin as a Key Regulator of NHEJ and PARP Inhibitor Sensitivity

Abstract: Repair of damaged DNA is essential for maintaining genome integrity and for preventing genome-instability-associated diseases, such as cancer. By combining proximity labeling with quantitative mass spectrometry, we generated high-resolution interaction neighborhood maps of the endogenously expressed DNA repair factors 53BP1, BRCA1, and MDC1. Our spatially resolved interaction maps reveal rich network intricacies, identify shared and bait-specific interaction modules, and implicate previously concealed regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
426
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(466 citation statements)
references
References 53 publications
37
426
1
2
Order By: Relevance
“…The EMBO Journal 38: e101379 | 2019 ª 2019 The Authors line with p53 being detected in APEX-based proximity labeling of 53BP1, but not of BRCA1 or MDC1 (Gupta et al, 2018). The gradual dilution of DSB-induced chromatin modifications away from the break site would thus establish functional divergence within the 53BP1 domain, with direct chromatin interactions governing the initial 53BP1 recruitment, and 53BP1 self-assembly-driven interactions toward the periphery.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The EMBO Journal 38: e101379 | 2019 ª 2019 The Authors line with p53 being detected in APEX-based proximity labeling of 53BP1, but not of BRCA1 or MDC1 (Gupta et al, 2018). The gradual dilution of DSB-induced chromatin modifications away from the break site would thus establish functional divergence within the 53BP1 domain, with direct chromatin interactions governing the initial 53BP1 recruitment, and 53BP1 self-assembly-driven interactions toward the periphery.…”
Section: Discussionmentioning
confidence: 80%
“…The DDR is initiated at DNA break sites by the ATM kinase, which phosphorylates histone variant H2AX to generate cH2AX (Shiloh & Ziv, 2013;Blackford & Jackson, 2017). Restrained resection is achieved by 53BP1dependent recruitment of RIF1, REV7, and the Shieldin complex (Dev et al, 2018;Findlay et al, 2018;Ghezraoui et al, 2018;Gupta et al, 2018;Mirman et al, 2018;Noordermeer et al, 2018;Setiaputra & Durocher, 2019). 53BP1 generates sizeable chromatin domains, which scaffold the assembly of downstream effectors and shield DNA lesions against excessive nucleolytic digestion.…”
Section: Introductionmentioning
confidence: 99%
“…By performing structure prediction analyses on SHLD2 protein sequence using Motif Scan (MyHits, SIB, Switzerland) and InterProScan5 (Jones et al , ), we identified a putative N‐terminal DNA‐binding domain (NUMOD3 domain) and a structural motif in its C‐terminus that we labeled PFAM (Fig A). Recently, structural prediction analyses of SHLD2 also defined a N‐terminal motif promoting protein–protein as well as three putative OB‐fold like domains at its C‐terminus (Dev et al , ; Ghezraoui et al , ; Gupta et al , ; Noordermeer et al , ; Tomida et al , ). Finally, previous phospho‐proteomic analysis identified a S/Q substrate of ATM/ATR following DNA damage at position 339 (Matsuoka et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…In BRCA1‐mutant cells, knockout of FAM35A allows recombination and/or alternative end‐joining repair pathways to be utilized more efficiently and helps explain the relative resistance to PARP inhibitors. Recently, a comprehensive survey of proteins associated with 53BP1 (Gupta et al , ) uncovered REV7‐binding proteins including FAM35A (designated RINN2). siRNA‐mediated suppression of BRCA1 in human U2OS cells increased their sensitivity to olaparib.…”
Section: Resultsmentioning
confidence: 99%